Perubahan iklim dan sistem manusia: Peran psikologi di mana? - Lestari, Made Diah; Wulanyani, Ni Made Swasti (Konsorsium Psikologi Ilmiah Nusantara, 2025)
Climate change is a global issue that affects human populations. This article discusses the psychological impacts of climate change and the role of scientist and practitioners in psychology in addressing this issue. Specifically, this article examines the specific effects of climate change on mental health, cognitive function, stress adaptation, psychiatric disorders, and increased suicidal tendencies. In terms of the role of psychology especially in Indonesia, this paper provides recommendations for initiating sustainable promotion, prevention, mitigation, and adaptation efforts within the scope of science and practice. This includes developing assessment tools for climate change risk and conducting basic research that informs evidence-based mitigation and adaptation strategies which accommodate local knowledge. A collaboration which accommodates multidisciplinary, multi stakeholder approach is imperative for implementing sustainable and evidence-based solutions.